2016
DOI: 10.1016/j.jds.2016.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical and radiographic study of the mandibular retromolar canal

Abstract: Background/purpose As the demand for surgical procedure in the retromolar area of the mandible has been increasing, the identification of the retromolar foramen (RMF) and canal involving the retromolar triangle (RMT) has become an issue of clinical concern. We examined the shape of the RMT, incidence of the RMF, and intraosseous trajectory of the retromolar canal (RMC). Materials and methods A total of 118 sides of dry mandibles, 22 sides of mandibles of 13 cadavers, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 16 publications
2
38
0
3
Order By: Relevance
“…The diversity between the dry mandible and fresh cadaver studies can be explained with the RMF being lost due to the atrophic changes in dried bone (Motamedi et al). Park et al (2016), reported that the prevalence of RMF was 33.6 % according to macroscopic examination of cadaver mandibles whereas the prevalence of RMF/RMC on CBCT was 11.5 %. They concluded that the ability to detect an RMC using CBCT is limited compared with direct anatomical observation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The diversity between the dry mandible and fresh cadaver studies can be explained with the RMF being lost due to the atrophic changes in dried bone (Motamedi et al). Park et al (2016), reported that the prevalence of RMF was 33.6 % according to macroscopic examination of cadaver mandibles whereas the prevalence of RMF/RMC on CBCT was 11.5 %. They concluded that the ability to detect an RMC using CBCT is limited compared with direct anatomical observation.…”
Section: Discussionmentioning
confidence: 99%
“…The RMC is positioned within or around the retromolar triangle (Park et al, 2016), branches from the main mandibular canal below the third molar and follows a recurrent path, curving in an anterior-superior direction behind the third molar to open in the retromolar foramen (RMF) (Ossenberg, 1987). The RMF is also found in the retromolar trigone, posterior to the last molar (Han & Park).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have reported different types of retromolar canals varying in their origin, course, and exit location [12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%